EVALUATION IN NEWS TEXTS IN UNIVERSITAS SEBELAS MARET’S OFFICIAL WEBSITE - Zhafira, Khansa Abi (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
The digital era and internationalization of higher education has led to the emergence of novel uses of new media such as the website where new higher education discourses emerge. This study examines the realization of evaluative language in English news texts in a university official website in the context of higher education. Using the Appraisal framework, this study attempts to identify lexicogrammatical resources construing attitude and graduation in eight news texts published in the official website of UNS from January to February 2019. The selected texts cover key news topics, namely reports of achievements, events, and a feature of a university facility. The findings show that attitudinal resources and its graduation are present in the news texts to create a positive image for UNS. Appreciation as the most prevalent type of attitude works to invoke positive judgement of capacity alongside inscribed judgement and affect to relay the image of UNS as a capable university. The study found that, while still following the structure of news texts, news writers for UNS’ official websites use various attitudinal resources in a complex system of prosody-creation to develop positive judgement towards the university’s capacity.